Kajian Hukum Pidana dan HAM Terhadap Tindak Kekerasan Aparat dalam Aksi Unjuk Rasa - Buldani, Muhammad Nahidh (LPPM Institut Pendidikan Nusantara Global, 2025)
Demonstrations are a form of citizen participation to express opinions in public spaces, as guaranteed by Article 28E of the 1945 Constitution and Law No. 9 of 1998. This activity is carried out verbally, in writing, or through other forms of expression as a means of opposing policies perceived to violate the law or human rights. Security forces are obligated to safeguard this right; however, in practice, acts of violence and repressive measures by the police are still frequently reported. According to reports from Amnesty International and the National Commission on Human Rights (Komnas HAM), incidents of torture continue to increase. Therefore, this study focuses on the aspects of criminal liability and human rights violations in the handling of public demonstrations. This research employs a normative juridical method through literature studies of legislation and legal literature. The aim is to explore legal principles, analyze norms, and interpret the applicable legal meaning using secondary sources such as books, journals, and official documents. The findings indicate that the handling of demonstrations by the police must be grounded in human rights principles and adhere to applicable laws. The discretionary authority outlined in Article 18 Paragraph (1) of Law No. 2 of 2002 is deemed vague and lacks clear limitations, making it prone to misuse. The violent crackdown during the 2024 “Kawal Putusan MK” protest highlights clear violations of human rights and criminal law. In practice, the constitutional right to freedom of expression is often violated.Therefore, revising the provisions on police discretion, reinforcing accountability, and strengthening the role of independent oversight are essential steps in safeguarding rights and upholding democracy.